Classification of the coefficient of variation for experiments with eucalyptus seedlings in greenhouse1 - Lopes, Beatriz Garcia; Faria, Glaucia Amorim [UNESP]; Maltoni, Katia Luciene [UNESP]; Rocha, Paula Suares [UNESP]; Peixoto, Ana Patrícia Bastos; de Oliveira, Tiago Almeida; da Fonseca, Ariéli Daieny [UNESP]; Felizardo, Lucas Menezes [UNESP]; Costa, Carlos Alexandre Gomes [UNESP] (GN1 Sistemas e Publicacoes, 2021)
In experimental statistics, the variability, which for conclusions related to experimental accuracy, is usually demonstrated by means of experimental coefficient of variation (CV). The aims of this study were to evaluate the distribution of CV in several experiments of eucalyptus growth, compare the existing classification ranges proposed in the literature (methods proposed by Garcia; Costa, Seraphin and Zimmermann, and Pimentel-Gomes), and define the better one to be used as reference for eucalyptus seedlings cultures in greenhouses or protected cultivation. For that, a blank test with 100 repetitions was conducted and evaluations were performed in 30, 60, 90 and 120 days. Moreover, previous data from literature were collected, for comparison proposes. The obtained results were submitted to Shapiro-Wilk and Kolmogorov-Smirnov tests, and the classification tables were submitted to adherence and heterogeneity tests. As a result, it was possible to conclude that data obtained with the experiments with eucalyptus in the present research did not fit the classification of Pimentel-Gomes and tables obtained by Costa, Seraphin and Zimmermann, while the tables related to the method proposed by Garcia would be preferably used.
Classificação do coeficiente de variação para experimentos com mudas de eucalipto em casa de vegetação
Keywords: Experimental precision. Experimental variation. Parametric tests. Non-parametric tests. E. grandis x E. urophylla; Precisão experimental. Variação experimental. Testes paramétricos. Testes não paramétricos. E. grandis x E. urophylla